A case of extensive acquired progressive lymphangioma. Issue 4 (6th April 2018) - Larkin, Sydney C.; Wentworth, Ashley B.; Lehman, Julia S.; Tollefson, Megha M.
Abstract: Acquired progressive lymphangioma (benign lymphangioendothelioma) is a rare lymphatic anomaly of unclear pathogenesis. Excision is generally advised for local disease, although other therapies have been tried. This report describes a unique case of extensive acquired progressive lymphangioma involving the abdomen, genitalia, and lower extremity of a 1‐year‐old boy. Rapid progression and multisite involvement required exploration of nonsurgical options for management.